VIOLENCE AND DEATH: THEIR INTERPRETATION BY K. A. PORTER AND EUDORA WELTY - Stegh Carnati, Anna (Revista Letras, 1983)
This study aims to elucidate the reasons for the prevalence of violence in Southern fiction. While K. A. Porter focuses violence as being a characteristic trait of the Southern temper, which can be traced back to the frontier days, Eudora Welty presents variations on the theme of spiritual isolation in her short-stories, which is connected with the conflicting world views of the forties: the confusion of values generated by the discrepancy existing between the ideal Southern society and the real world of the South results in violence. Similar tensions to those of the American South are evoked by K. A. Porter in her Mexican stories. The different connotations of death, both symbolic and real, are also analysed in this study, showing that the recurrence of the death motif has to do with the Southerner's metaphysical preoccupations.